Finite‐time adaptive fuzzy control for induction motors with input saturation based on command filtering. Issue 15 (1st October 2018) - Han, Yao; Yu, Jinpeng; Zhao, Lin; Yu, Haisheng; Lin, Chong
Abstract : This study develops a fuzzy finite‐time command filtered position tracking control approach for induction motors with input saturation. First, the fuzzy logic systems are utilised to approximate the non‐linear functions. Then, in order to avoid the 'explosion of complexity' in backstepping design, the finite‐time command filter is employed. In addition, error compensating signals are introduced to decrease the errors produced by command filters. The fuzzy finite‐time adaptive command filtered controllers can guarantee that the tracking error can converge in finite time. The results of simulation show the effectiveness of the proposed method.